The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1182/blood.v80.12.3060.bloodjournal80123060
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-macrophage colony-stimulating factor and erythropoietin act competitively to induce two different programs of differentiation in the human pluripotent cell line UT-7

Abstract: The UT-7 cell line was established from a patient with a megakaryoblastic leukemia (Komatsu et al, Cancer Res 51: 341, 1991). Its proliferation is strictly dependent on the presence of hematopoietic growth factors including erythropoietin (Epo), granulocyte-macrophage colony-stimulating factor (GM-CSF), and interleukin-3 (IL-3). We investigated the differentiation capacities of this cell line under the action of several growth factors, using immunomarkers, flow cytometry, and ultrastructural techniques. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…Our data suggested that the three cytokines TPO, GM-CSF and EPO, activate similar JAK/STATs pathway in the same cell, since all activate JAK2 and not JAK1 (this report; Ihle et al, 1994) and all three activate STAT5 and not STAT1-4 (this report;Lamer et al, 1993;Yamamoto et al, 1994). Since these three cytokines induce cell proliferation of the UT7 cells but trigger different differentiation programs (Hermine et al, 1992; and unpublished data), our results would be consistent with a role of JAK2/STAT5 in cell proliferation rather than in cell differentiation. This hypothesis is further strengthened by our findings that PRL and IL-3-which mainly allow the hematopoietic BAF-3 cells to proliferate-also activate STAT5 in BAF-3 cells, and by the possible activation of STAT5 by a number of other cytokines (see above).…”
Section: Discussionsupporting
confidence: 85%
“…Our data suggested that the three cytokines TPO, GM-CSF and EPO, activate similar JAK/STATs pathway in the same cell, since all activate JAK2 and not JAK1 (this report; Ihle et al, 1994) and all three activate STAT5 and not STAT1-4 (this report;Lamer et al, 1993;Yamamoto et al, 1994). Since these three cytokines induce cell proliferation of the UT7 cells but trigger different differentiation programs (Hermine et al, 1992; and unpublished data), our results would be consistent with a role of JAK2/STAT5 in cell proliferation rather than in cell differentiation. This hypothesis is further strengthened by our findings that PRL and IL-3-which mainly allow the hematopoietic BAF-3 cells to proliferate-also activate STAT5 in BAF-3 cells, and by the possible activation of STAT5 by a number of other cytokines (see above).…”
Section: Discussionsupporting
confidence: 85%
“…The levels of PtdIns 3-kinase stimulation produced by the various growth factors could be explained, at least in part, by the relative number of growth-factor membrane receptors. UT7 cells exhibit only 200 high-affinity GM-CSF receptors, 7000 erythropoietin receptors [41] and more than 60000 SCF receptors (Mayeux, P., unpublished results). The number of IL-3 and IL-6 receptors has not been determined.…”
Section: Discussionmentioning
confidence: 98%
“…EPO and GM-CSF, for example, both induce the same factor in the multipotential hematopoietic cell line UT7. Both cytokines induce the proliferation of UT7 cells, but the cytokines have distinct effects on the differentiation of UT7 cells (Komatsu et al, 1991;Hermine et al, 1992). It is reasonable to suggest that MGF-StatS activation might be important for the common effect, proliferation, via the regulation of an overlapping subset of target genes induced by EPO and GM-CSF.…”
Section: Discussionmentioning
confidence: 99%